The impact of simulation training on enhancing the understanding of providing aid for injury cases among the Healthy Student Cadres (HSCs) at Assalafiyyah II Mlangi Islamic Boarding School - Farhany, Fajrul Falah; Ichwan, Ichwan; Ernia, Winda; Widianingrum, Setiyati; Arifah, Naily Zahrotun; Rinonce, Hanggoro Tri; Kusumawati, Happy Indah; Muslichah, Rahadyana (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Introduction: The students of Islamic boarding Schools, as agents of change, often experience complaints of muscle and joint injuries. Assalafiyyah II Mlangi Islamic Boarding School (IBS) was one of the pioneers of an integrated health system to improve health status. However, the condition of health facilities, especially those related to handling injuries, was still very minimal. In addition, the students had never received counseling regarding injury management. Therefore, it is necessary to conduct research related to the effect of health education in increasing knowledge about assisting in cases of injury to Healthy Student Cadres (HSCs) of Assalafiyah II Mlangi IBS. This study aimed to determine the effect of health education in increasing knowledge about assisting in cases of injury to healthy students Cadres Assalafiyyah II IBS. Methods: This study was carried out using a quantitative experimental design. A one-group, quasi-experimental pretest-posttest approach was adopted in this study. The 40 healthy student cadres from Assalafiyyah II Mlangi IBS were recruited. The knowledge scores of the pretest (before health education) and post-test (after health education) were compared using the paired sample t-test. Furthermore, the Kruskal-Wallis test examined the relationship between education level and knowledge score. Results: The pretest results showed that the level of knowledge of the subjects in the good category was 5%, adequate was 30%, and poor was 65%. In contrast, the post-test results showed an increase in knowledge scores. In particular, subjects in the good category were 47.5%, adequate was 40%, and poor were as much as 12.5%. This study also showed a significant change in the score of knowledge about assisting in cases of injury to subjects after providing health education in a positive correlation with p= 0.000. The level of education did not affect the results of the knowledge score about assisting in injury cases, with p= 0.072. Conclusion: Providing health education materials effectively increases knowledge about helping Healthy Student Cadres (HSCs) in injury cases. This increase in knowledge can make Healthy Student Cadres (HSCs) pioneers in the surrounding environment regarding the importance of assisting in injury cases.